Host pharmacokinetics and drug accumulation of anthelmintics within target helminth parasites of ruminants - Lifschitz, Adrian Luis (2017)
Anthelmintic drugs require effective concentrations to be attained at the site of parasite location for a certain period to assure their efficacy. The processes of absorption, distribution, metabolism and excretion (pharmacokinetic phase) directly influence drug concentrations attained at the site of action and the resultant pharmacological effect. The aim of the current review article was to provide an overview of the relationship between the pharmacokinetic features of different anthelmintic drugs, their availability in host tissues, accumulation within target helminths and resulting therapeutic efficacy. It focuses on the anthelmintics used in cattle and sheep for which published information on the overall topic is available; benzimidazoles, macrocyclic lactones and monepantel. Physicochemical properties, such as water solubility and dissolution rate, determine the ability of anthelmintic compounds to accumulate in the target parasites and consequently final clinical efficacy. The transcuticular absorption process is the main route of penetration for different drugs in nematodes and cestodes. However, oral ingestion is a main route of drug entry into adult liver flukes. Among other factors, the route of administration may substantially affect the pharmacokinetic behaviour of anthelmintic molecules and modify their efficacy. Oral administration improves drug efficacy against nematodes located in the gastroinestinal tract especially if parasites have a reduced susceptibility. Partitioning of the drug between gastrointestinal contents, mucosal tissue and the target parasite is important to enhance the drug exposure of the nematodes located in the lumen of the abomasum and/or small intestine. On the other hand, large inter-animal variability in drug exposure and subsequent high variability in efficacy is observed after topical administration of anthelmintic compounds. As it has been extensively demonstrated under experimental and field conditions, understanding pharmacokinetic behaviour and identification of different factors affecting drug activity is important for achieving optimal parasite control and avoiding selection for drug resistance. The search for novel alternatives to deliver enhanced drug concentrations within target helminth parasites may contribute to avoiding misuse, and prolong the lifespan of existing and novel anthelmintic compounds in the veterinary pharmaceutical market.